2010
DOI: 10.1002/adfm.201001292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Annealing and Interfacial Roughness on the Performance of Bilayer Donor/Acceptor Polymer Photovoltaic Devices

Abstract: Through controlled annealing of planar heterojunction (bilayer) devices based on the polyfluorene copolymers poly(9,9‐dioctylfluorene‐co‐bis(N,N′‐(4,butylphenyl))bis(N,N′‐phenyl‐1,4‐phenylene)diamine) (PFB) and poly(9,9‐dioctylfluorene‐co‐benzothiadiazole) (F8BT) we study the influence of interface roughness on the generation and separation of electron–hole pairs at the donor/acceptor interface. Interface structure is independently characterized by resonant soft X‐ray reflectivity with the interfacial width of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 49 publications
2
125
0
Order By: Relevance
“…Models of this type have been shown to agree quantitatively with J-V curves of polymer bilayer OPV devices with abrupt 30 and roughened 31 interfaces. In the model, the OPV was represented as a 3D…”
Section: Monte Carlo Simulationsmentioning
confidence: 76%
See 2 more Smart Citations
“…Models of this type have been shown to agree quantitatively with J-V curves of polymer bilayer OPV devices with abrupt 30 and roughened 31 interfaces. In the model, the OPV was represented as a 3D…”
Section: Monte Carlo Simulationsmentioning
confidence: 76%
“…It is noted that this recombination rate is the same as that used in a similar Monte Carlo model which obtained quantitative agreement with experimental J-V data for an amorphous all-polymer OPV 30 . These parameters are expected to mimic the situation which occurs in amorphous all-polymer OPVs, in which field-activated  GS has been reported 30,31,35 . This choice of parameters is deliberate since binary blends of amorphous materials are unlikely to form cascaded energy heterojunctions, therefore one can be reasonably confident that these parameters are free from the potential effects of energy cascades.…”
Section: Monte Carlo Simulationsmentioning
confidence: 87%
See 1 more Smart Citation
“…This is in particular related to the fact that a lower number of defects at the interface facilitates higher charge carrier mobilities [19][20][21][22]. As we have seen above films formed by upright After reaching a critical coverage, the structure changes to a bulk like molecular arrangement.…”
Section: Layer-by-layer Growth Of Lying Moleculesmentioning
confidence: 84%
“…Hence for OPVs which rely on conventional exciton dissociation, nano-structured morphologies are required, and device models have been used extensively to understand which forms of morphology are most favourable. As well as bilayers [73,143,377], morphologies examined include interdigitated pillars [48,201,[378][379][380], gyroids [381], idealised BHJs [48, 147,201,380] and non-ideal BHJs [114,123,382,383]. It is shown that interdigitated pillars have highest performance, since the electric field is either parallel or perpendicular to the plane of the heterojunction, while perhaps unexpectedly, gyroid and idealised BHJ morphologies have very similar performance [381].…”
Section: 2mentioning
confidence: 99%